Effects of physical activity on carbohydrate and lipid metabolism in women withabdominal obesity - Kasprzak, Zbigniew; Pilaczyńska-Szcześniak, Łucja (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The incidence of metabolic disorders in obese people is not only determined by the amount of adipose tissue but mainly by its distribution. Metabolic disorders may lead to the development of occupational metabolic diseases. Aim of Study. The aim of the study was to estimate the effects of increased physical activity in women with abdominal obesity on carbohydrate and lipid metabolism and glucose tolerance. Material and Methods. The study was carried out on a group of 32 physically active women aged 59.1 ± 5.39 years. Somatic traits were measured and physiological and biochemical tests (VO2 max, lipid profile, glucose and insulin levels) were carried out at rest while fasting. The BMI, WHR and HOMAIR indices were calculated. Results. The following results were obtained for the sample: BMI (32.9 ± 4.57 kg/m2), WHR (0.88 ±0.04), VO2max (33.6 ± 8.19 ml/kg-1/min–1), total cholesterol (226.3 ± 45.12mg/dl), LDL-cholesterol (140.6 ± 37.79 mg/dl). Conclusions. The results confirm positive effects of physical activity on the lipid profile and the homeostatic model assessment insulin resistance index (HOMAIR).
Keywords: abdominal obesity; physical activity; lipid profile; HOMAIR